'Spiritualized Islam': Reconfigurations of Islamic Dogma Among Young Non-Organized Muslims in Norway. Issue 1 (2nd January 2021) - Aarvik, Signe
ABSTRACT: This article provides examples of how some young Muslims in Norway reconfigure Islamic norms and doctrines in the direction of contemporary spirituality. These young Muslims' beliefs include elements of 'objective' Islamic dogma, while simultaneously sacralizing the significance and authority of subjective life to the degree that it challenges established orthodoxy. Their interpretations of Islam may be described as a synthesis of two fundamentally different approaches to the sacred, namely 'life-as-religion' and 'subjective-life spirituality', as described in the work of Linda Woodhead and Paul Heelas. An emphasis on the symbolic, abstract and ambiguous character of religious dogma allows for not only a high degree of subjective interpretation, but also a pluralist attitude towards other religions and worldviews. Aspects of the interviewees' life-stories suggest that spiritualization of Islam is linked to concerns with inclusion in liberal-secular and pluralistic social settings. It is argued that the tendency towards spiritualization represents a trajectory among young European Muslims that is distinct from the already well-defined tendencies of secularization and Islamic revitalization.